2018
DOI: 10.24914/jeb.v21i2.1821
|View full text |Cite
|
Sign up to set email alerts
|

Studi empiris pengaruh kepuasan kerja, turnover intention, produktivitas, dan keunggulan bersaing

Abstract: Penelitian ini difokuskan pada karyawan CV Duta Jepara, sebuah perusahaan mebel di Kabupaten Jepara, untuk menguji pengaruh kepuasan kerja dan turnover intention terhadap produktivitas serta keunggulan bersaing perusahaan. Penelitian ini mengolah data primer yang diperoleh menggunakan kuesioner yang dibagikan kepada 468 karyawan. Sampel penelitian dipilih menggunakan metode purposive sampling dengan pertimbangan karyawan dari departemen produksi yang sudah bekerja lebih dari dua tahun. Sampel yang dianalisis s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(8 reference statements)
1
0
0
Order By: Relevance
“…The findings of this study corroborate those of studies (Fu'ada & Gumilar, 2018) that found turnover intention had no impact and is not significantly different from zero impact on job productivity. This study also highlights how increased turnover rates hinder a company's ability to expand and flourish each time an employee leaves.…”
Section: The Effect Of Turnover Intention On Work Productivitysupporting
confidence: 90%
“…The findings of this study corroborate those of studies (Fu'ada & Gumilar, 2018) that found turnover intention had no impact and is not significantly different from zero impact on job productivity. This study also highlights how increased turnover rates hinder a company's ability to expand and flourish each time an employee leaves.…”
Section: The Effect Of Turnover Intention On Work Productivitysupporting
confidence: 90%